2016
DOI: 10.3847/0004-637x/824/1/35
|View full text |Cite
|
Sign up to set email alerts
|

New Spectroscopic Technique Based on Coaddition of Surface Brightness Fluctuations: NGC 4449 and Its Stellar Tidal Stream

Abstract: We present a new spectroscopic technique based in part on targeting the upward fluctuations of the surface brightness for studying the internal stellar kinematics and metallicities of galaxies of low surface brightness effects both to galaxies and streams beyond the Local Group. The distance to these systems makes them unsuitable for targeting individual red giant branch (RGB) stars (tip of RGB at  I 24 mag) and their surface brightness is too low (  m 25 r mag arcsec −2 ) for integrated light spectroscopic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 70 publications
(104 reference statements)
0
28
0
Order By: Relevance
“…On the other hand, Martínez-Delgado et al (2012) and Rich et al (2012) detected and analyzed a stellar tidal stream in the halo of NGC 4449, arguing that this object is the result of the ongoing disruption of a dSph galaxy, while Annibali et al (2012) found a globular cluster of NGC 4449 which appears associated with two tails of blue stars, possibly the nucleus of a former gas-rich satellite galaxy undergoing tidal disruption by NGC 4449. Finally, using metallicity measurements of the stream, Toloba et al (2016) suggested a progenitor as massive as Fornax or Sagittarius. Interestingly, an interaction like that could have had a substantial impact on NGC 4449.…”
Section: Ngc 4449mentioning
confidence: 99%
“…On the other hand, Martínez-Delgado et al (2012) and Rich et al (2012) detected and analyzed a stellar tidal stream in the halo of NGC 4449, arguing that this object is the result of the ongoing disruption of a dSph galaxy, while Annibali et al (2012) found a globular cluster of NGC 4449 which appears associated with two tails of blue stars, possibly the nucleus of a former gas-rich satellite galaxy undergoing tidal disruption by NGC 4449. Finally, using metallicity measurements of the stream, Toloba et al (2016) suggested a progenitor as massive as Fornax or Sagittarius. Interestingly, an interaction like that could have had a substantial impact on NGC 4449.…”
Section: Ngc 4449mentioning
confidence: 99%
“…MOSAIC will deliver several advances in the field by measuring the stellar kinematics in z~1 galaxies or in sub-structures of local systems. In particular, measuring the stellar kinematics of the tidal debris expected to lie in the outskirts of most Milky Way-like systems will allow us to test theoretical predictions and learn about the processes by which these galaxies formed (Toloba et al 2016), and provide unique views on their dark matter halos (Errani et al 2015). At earlier epochs (2<z<4), it will be important to measure spatially-resolved chemodynamical information in galaxies across a wide range of stellar masses (dwarfs to giants) and environments (field to clusters).…”
Section: Mosaic Science Case Before Prioritisationmentioning
confidence: 99%
“…To improve the reliability of v we coadd all 27 stars together (see Figure 2). Our spectral coaddition process is the same one as described by Toloba et al (2016a): (1) correct for possible offsets across the slit using the atmospheric A band seen in the continuum of all objects, this correction is < 10 km s −1 ; (2) rebin the spectra and their uncertainties to a common wavelength range; (3) renormalize the fluxes and their associated uncertainties; and (4) add, pixel by pixel, the fluxes of the renormalized rebinned spectra by performing a sigma clipping where those pixels that deviate more than 3σ from the median are rejected.…”
Section: Radial Velocitymentioning
confidence: 99%
“…We estimate the stellar metallicity of d0944+71 following the same procedure as Ho et al (2015) and Toloba et al (2016a). This method transforms the equivalent width (EW) of the two strongest absorption Upper panels: flux (dark green) and error (light green) spectra that result after coadding all 27 targets used to measure the radial velocity of d0944+71.…”
Section: Metallicitymentioning
confidence: 99%
See 1 more Smart Citation